Topological exciton-polaritons without a magnetic field - Seet, Nathan Wei En (Nanyang Technological University, 2021)
Exciton-polaritons are hybrid particles composed of a superposition of photons and excitons. Through pumping schemes, resonant or non-resonant pumping, they can undergo a phase transition to form a Bose-Einstein Condensate. In this superfluid phase, vortices have been observed in polariton systems. Past research has shown that a system of interacting lattice of vortices can induce a topological behaviour. This scheme, however, requires the use of a resonant pump. Recently, an experimental work showed that vortices can be imprinted by a non-resonant pump. However, there are no theoretical models explaining this phenomenon yet. In this report, we want to develop a new theoretical model to explain the experimental findings and incorporate them with past research to predict if a lattice of vortices generated by this scheme can induce a topological behaviour.